Complexity and impediments in the physical level for the implementation of cognitive satellite networks (Revista de Investigaciones Universidad del Quindío, 2012)
In this paper some impediments that are currently on the physical level to implement cognitive satellite networks are show. Further illustrated from the standpoint of game theory as can be optimally implemented some of the cognitive functions required in these systems. The basic functions of a satellite and / or cognitive earth station are: flexibility, reconfigurability, auto-configurability, dynamic spectrum access, adaptation and learning of environmental conditions to optimize the use of radio resources. Some of these functions can be implemented through radio software, however, the most of them require high processing capabilities, high computational costs and very low response times, which in many cases prevents its implementation
Keywords: Learning; Resource Allocation; Quality of Service; Cognitive Radio; Software Defined Radio DSP; FPGA; Cognitive Satellite Networks; Base Station